Hubungan Status Kepegawaian Dan Masa Kerja Staf Unit Kerja Rekam Medis Dengan Produktivitas Kerja Di Blud RSU Dr. H. Moch Ansari Saleh Banjarmasin - Rusman Efendi; Hosizah Hosizah; Lisda Novilia; STIKES Husada Borneo; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2015)
Introduction: Every organization wants to have high motivated labors and optimal productivity, punctuality and objectified implementation, all in harmony, so that the labor productivity can be acquired maximally. Thus, the objective of this research is to find out the correlation between labor’s working status and working period with their productivity in Dr. H. Moch. Ansari Saleh State Hospital Banjarmasin.Method: Type of research used in this research is correlation research with cross-sectionaldesign. The research is done to 18 correspondents in medical record unit; the instrumentations are observation and questioner.Result: Based on the research on working status, there are 38,8% state labors and 61,1 non - state labors. While the research for working period acquires data that < 1 year working period is 16,6%, 1-5 years working period is 33,3% and > 5 years working period is 50%. As for the labor productivity, there are 77,77% in high productivity, 11,11% in average productivity and 11,11% in low productivity.Based on the statistic calculation with several variables using exact fisher test shows the correlation between working status and labor productivity is P= 0,137 > alpha=0,05. It means there is no significant correlation between those two variables. In addition, the exact fisher test calculation between working period and labor productivity is P=0,471 > alpha=0,05. It means there is no significant correlation between those variables.